The bungled digitisation of Healthy Start is hampering low income families' access to healthy food. (14th June 2022) - Defeyter, Margaret Anne; Hetherington, Marion; McKean, Mike; Forsey, Andrew
Abstract : For months, families have reported problems with the digital transition of Healthy Start, a government funded programme to support families on low incomes. As the cost of living crisis worsens, this is leading to avoidable hardship, write Margaret Anne Defeyter and colleagues